A new strategy to design eutectic high-entropy alloys using mixing enthalpy. (December 2017) - Lu, Yiping; Jiang, Hui; Guo, Sheng; Wang, Tongmin; Cao, Zhiqiang; Li, Tingju
Abstract: Although eutectic high entropy alloys (EHEAs) display homogeneously fine microstructure, excellent castability and promising industrial application potential, how to design eutectic compositions in high entropy alloys (HEAs) remains to be challenging. Here, a novel strategy, specifically, through calculation of mixing enthalpy, was used to locate eutectic compositions in HEAs. As a proof of this concept, a series of EHEAs were located and prepared following the mixing enthalpy method. Using this new strategy, eutectic compositions can be designed conveniently, once one can classify elements into two different groups. This new alloy design strategy can be readily adapted to locate new EHEAs. Graphical abstract: Highlights: A new strategy to design eutectic high-entropy alloys was proposed using mixing enthalpy method. A series of eutectic high-entropy alloys were located and prepared following the method. Using this new strategy, eutectic compositions can be designed conveniently.